1991
DOI: 10.1016/0014-5793(91)81059-h
|View full text |Cite
|
Sign up to set email alerts
|

ADP/ATP translocator is essential only for anaerobic growth of yeast Saccharomyces cerevisiae

Abstract: All three genes (AACl.AAC2and AAC3) encoding the mitochondrial ADP/ATP translocator. were inactivated in a haploid yeast strain by a gene disruption technique. The triple mutant was still able to grow on fermentable carbon sources but only in the presence of oxygen. Under aerobic conditions neither translocator-protein nor carrier-mediated transport was detected in all mutants in which the AAC2 gene was disrupted. It was further shown that a functional AAC genes product is essential only for anaerobic growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 14 publications
2
86
0
Order By: Relevance
“…This ®nding is consistent with the absence of cytochrome c translocation in r 0 cells, while dissociation between cytochrome c release and mitochondrial potential change has been reported (Bossy-Wentzel et al, 1998). Previous papers employing mammalian cells or yeast reported that mitochondrial potential is preserved in mitochondrial DNA-depleted cells, owing to compensatory adenine nucleotide translocator function allowing countertransport of adenine nucleotides across the mitochondrial membrane (Buchet and Gedinot, 1998;Drgon et al, 1991;Skowronek et al, 1992). No signi®cant basal and glucose-stimulated mitochondrial proton gradient previously observed in SK-Hep1 r 0 cells might be due to the di erence in the method of measurement between¯ow cytometry and quenching method (Park et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…This ®nding is consistent with the absence of cytochrome c translocation in r 0 cells, while dissociation between cytochrome c release and mitochondrial potential change has been reported (Bossy-Wentzel et al, 1998). Previous papers employing mammalian cells or yeast reported that mitochondrial potential is preserved in mitochondrial DNA-depleted cells, owing to compensatory adenine nucleotide translocator function allowing countertransport of adenine nucleotides across the mitochondrial membrane (Buchet and Gedinot, 1998;Drgon et al, 1991;Skowronek et al, 1992). No signi®cant basal and glucose-stimulated mitochondrial proton gradient previously observed in SK-Hep1 r 0 cells might be due to the di erence in the method of measurement between¯ow cytometry and quenching method (Park et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Published procedures were used for preparation of total RNA from yeast cells [14], protein extraction from yeast cells [16], immuno-blot analysis of AAC proteins [4], and transformation of yeast cells by lithium acetate treatment [17]. For the Northern blots, total RNA was electrophoresed on a denaturing 1.2% agarose gel containing formaldehyde [14].…”
Section: Methodsmentioning
confidence: 99%
“…myces cerevisiae, it is also essential for growth under anaerobic conditions [4]. Previous studies have indicated that the content of ADP/ATP carrier in the mitochondrial membrane is affected by the growth conditions, and by mitochondrial-respiratory-deficient (e-) mutations [5-71.…”
mentioning
confidence: 99%
“…While AACI and AAC2 are expressed preferentially )ruder derepressed conditions, the AAC3 gone is expressed only under anaerobic conditions [3]. Among these three genes only AAC2 encodes a translocator protein functioning in the ADP/ATP transport during oxidative phosphorylation [2][3][4][5][6]. On the other hand the AAC1 and AAC3 genes are not essential for growth on respiratory carbon sources and their products cannot be detected in the mitochondria of cells grown under different conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among these three genes only AAC2 encodes a translocator protein functioning in the ADP/ATP transport during oxidative phosphorylation [2][3][4][5][6]. On the other hand the AAC1 and AAC3 genes are not essential for growth on respiratory carbon sources and their products cannot be detected in the mitochondria of cells grown under different conditions [4]. Thus, the cellular function of the products of the AACl and AAC3 genes remains unclear.…”
Section: Introductionmentioning
confidence: 99%